Pasar Uang Berdasarkan Prinsip Syariah di Indonesia - Maryam Batubara; Purnama Ramadani Silalahi ; Muhammad Al Fazri; Aulia Monica; Sakinah Sakinah (LPPM IAI Nasional Laa Roiba Bogor, 2022)
The money market is a gathering place between parties who have excess assets and individuals who experience a lack of assets, the system is by exchanging temporary assets into certain assets with developments in less than one year. In the money market, the application actually involves revenue to create profit. Therefore, progress is needed in the exchange of currency markets using the Qur'an and Hadith as a premise. Also currently there is a sharia money market and has received the legitimacy of the National Sharia Council (DSN) fatwa No. 37 concerning the interbank money market with sharia standards as an answer to the need for exchange rates, especially for Muslim community groups. Keywords: Money market, Islamic money market, DSN-MUI fatwa.